Leveraging psychometric properties of Ubuntu measures to reveal its structural components - Renier Steyn; Pumela Msweli (Interdisciplinary Journal of Sociality Studies)
Ubuntu is an African worldview that often shapes policy and social ethos; however, its distinct meaning remains unclear due to primarily philosophical discussions. This study seeks to define and measure Ubuntu's dimensions operationally and quantitatively using psychometric literature. Limited conceptual clarity has hampered research on Ubuntu thus far. This study aims to define Ubuntu, considering the materialisation of the concept and its components when measured, and to provide a usable measurement tool to advance research. A comprehensive review of Ubuntu measurement tools was conducted, focusing on research that included discussions of exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and measurement invariance (MI). Five Ubuntu measures were identified, revealing similar constructs but inconsistent terminology. EFA helped refine constructs, while CFA validated frameworks. MI was applied once, demonstrating cross-context adaptability. This study reveals that Ubuntu is frequently described as having more structural components than those that emerge from psychometric scrutiny and calls for a standardised framework and an agreed-upon, consistent measure of Ubuntu to advance empirical research. It provides a foundational list of items for a comprehensive measure, bridging the gap between philosophical and empirical approaches to Ubuntu.